Vitamin K deficiency evaluated by serum levels of undercarboxylated osteocalcin in patients with anorexia nervosa with bone loss. Issue 3 (June 2015) - Urano, Ayako; Hotta, Mari; Ohwada, Rina; Araki, Mariko
Summary Background & aims Osteoporosis is a chief complication in patients with anorexia nervosa. Serum levels of undercarboxylated osteocalcin reflect serum and bone vitamin K deficiency. We investigated vitamin K status in patients with anorexia nervosa to help establish prevention and treatment recommendations for osteoporosis. Methods Fifty-four female amenorrheic patients with anorexia nervosa (29 restricting-type and 25 binge eating/purging type) (age, 28.0 (26.7–31.1) (mean (95% CI)) years; body mass index, 14.8 (14.1–15.5) kg/m2, duration of illness; 107.3 (88.5–126.0) months) and 15 age-matched healthy females were included in this study. We measured serum levels of undercarboxylated osteocalcin, biochemical and nutritional markers, and bone metabolic markers. Dietary vitamin K intake was evaluated by a questionnaire. Results Lumbar bone mineral density and T-scores in patients with anorexia nervosa were 0.756 (0.721–0.790) g/cm2 and −2.4 (−2.1 to −2.7), respectively, indicating bone loss. Serum levels of undercarboxylated osteocalcin in patients with anorexia nervosa were significantly higher than those of controls. The 17% of restricting type and 40% of binge eating/purging type anorexia nervosa patients, serum levels of undercarboxylated osteocalcin were higher than 4.5 ng/ml and were diagnosed with vitamin K deficiency. Serum levels of undercarboxylated osteocalcin correlated significantly and negatively with vitamin K intake in patients with anorexia nervosa. Conclusions Patients with anorexia nervosa had vitamin K deficiency. Since a supplement of vitamin K might be effective for maintaining bone quality, we provide recommendations regarding vitamin K intake for prevention and treatment of osteoporosis in patients with AN.